En tunne itseäin ; Ilman rakkautta - Simola, Seija, 1944-2017; Discophon ([Kustannuspaikka tuntematon] : Discophon, 1982)
2 kappaletta.
Seija Simola (lauluääni).
[Äänite].
Keywords: Simola, Seija, -- 1944-2017 -- singlet; viihdemusiikki